Business Model Canvas Strategy Analysis in Technology-Based Startups - Kirana, Belva; Dara, Dyana; Lestari, Naura Citra (IHSA Institute, 2026)
The rapid growth of technology-based startups in the digital economy highlights the importance of having a well-structured and strategic business model to ensure sustainability and competitiveness. However, many startups fail due to unclear value propositions, weak revenue models, and poor alignment between business components. This study aims to analyze the business strategy of a technology-based startup using the Business Model Canvas (BMC) framework. The research adopts a qualitative case study approach, with data collected through interviews, observations, and documentation, and analyzed using the nine elements of the BMC. The findings reveal that the startup demonstrates strengths in its value proposition, digital channels, and scalability, enabling it to effectively deliver services to its target market. However, weaknesses are identified in the alignment between customer segments and value propositions, as well as in the design of revenue streams that may not fully meet customer expectations. These gaps indicate the need for better strategic integration across business model components. The study concludes that the Business Model Canvas is an effective tool for systematically analyzing and improving startup strategies, particularly when used not only for planning but also for continuous evaluation and innovation to enhance long-term business performance and sustainability.